Development of Curriculum and Learning Management in Training and Intensive Courses of Arabic Language Program l Tatwir al-Manahij wa Idarah al-Ta’lim fi-Baramij al-Tadrib wa al-Tatwir wa al-Daurat al-Mukassafah li-Lugah al-‘Arabiyyah - Inayah, Inayah; Husna, Muhammad Ahsanul; Sujai, Sujai; Istiqomah, Z.sie Nurul; Sutiah, Sutiah; Syuhadak, Syuhadak (Universitas Islam Negeri Raden Intan Lampung, 2023)
Curriculum development and learning management played a crucial role in maintaining quality and aligning with formulated objectives. The study aimed to analyze the curriculum and management of intensive course programs as well as training and development programs. A qualitative field analysis with a comparative approach was employed as the research method. Data were collected through observation, interviews, and documentation, and the data analysis involved descriptive analysis of curriculum and management aspects. The findings revealed that Al-Azhar's intensive course integrated both classical and modern curriculum elements, whereas the UIN Walisongo language development center focused exclusively on language standardization exam preparation (IMKA). The Arabic Online program demonstrated effective organization, incorporating periodic evaluations at each level leading to a world-standard language certificate upon completion. Concerning curriculum aspects, the UIN Walisongo Language Centre courses were identified as needing improvement in materials, learning exercises, and the development of more diverse course formats. Additionally, alignment of vision and mission between leaders and course teachers was recommended. This research contributed valuable insights to the development of curriculum and learning management in Arabic language intensive courses and training programs.